Testing Applicability of Point Merge Systems for Göteborg Landvetter Airport - Hardell, Henrik; Polishchuk, Tatiana; Smetanová, Lucie (Journal of Open Aviation Science, 2025)
The ability to comprehensively evaluate the performance inside Terminal Maneuvering Area (TMA) is important for understanding of the traffic conditions in the airport vicinity, and to identify the areas for possible improvements. We examine performance of the individual arrival flows to Göteborg Landvetter airport and analyze them separately in order to identify the problematic areas. Then, we test the potential of introducing Point Merge (PM) arrival procedure to this airport and schedule aircraft arrivals along them. We aim to determine whether introducing the PM structure improves the arrival performance and analyze the associated trade-offs. Comparing the resulting performance of the optimally-scheduled arrivals with PM against the baseline scenario derived from the historical flight trajectories obtained from the open-source Opensky Network database, we observe that adherence to the PM procedures provides a decrease in the fuel consumption about 5% in average due to improved vertical efficiency, however the time and distance aircraft spend in TMA increased both 10.4%. PM usage provides additional benefits in terms of improved controllability of the traffic flows, supported by significant reduction in the spacing deviation within the control area close to the runway.